ANALISIS PENERAPAN DIMENSI KONVERGENSI TERHADAP SUARA SURABAYA MEDIA - Holatila, Christian Steven Dylano; Winata, Muhammad Danu (Universitas Negeri Surabaya, 2025)
Digital Disruption drives the transition in the Mass Media Industry workflow from analog to digital. Every type of conventional mass media needs to innovate in order to develop with the times while maintaining its identity. Mass Media Convergence is one of the steps that conventional mass media companies need to take in order to increase relevance, while maintaining their existence. As a form of conventional media, radio also experiences difficulties in maintaining its existence and relevance to the digital community. International radio companies to national radio companies in Indonesia experience the same challenges, as do local radio. Suara Surabaya is one example of a local radio that since its inception has realized the importance of growing with technological developments, developing digital reach and integrating each platform it has through the implementation of Media Convergence. The results of this implementation make Suara Surabaya as a local radio able to maintain its existence and relevance amidst the onslaught of digital media. This study aims to analyze the implementation of Suara Surabaya Convergence according to the classification of each dimension of convergence, including: Ownership Convergence, Tactical Convergence, Structural Convergence, Information - Gathering Convergence, & Structural Convergence. The results of this study show the relationship between the existence of Suara Surabaya and the implementation of Convergence, and examine in detail the management of Suara Surabaya Media Convergence.